Thermodynamic assessment of washoil polymer formation - Bannikov, A. L. (My University, 2023)
Qualitative assessment of degradation processes of recycled wash oil during operation of benzene units allows to establish the influence of technological factors on oil specific consumption and to evaluate the quality of fresh oil by additional parameters. The main factors of the processes affecting the yield of resin like substances and the q uality of wash oil were determined.
Keywords: washing oil; resins; polymerization; thermodynamic evaluation